Making an Infamous Love Story Sing: Translating Bonnie and Clyde the Musical into Spanish - Purslow, Alannah (Trinity College Dublin, 2024)
Bonnie and Clyde are undoubtedly one of the most notorious murderous couples. Their names are internationally recognised and curiosity about their life and times has continued to intrigue people over the intervening decades. This dissertation aims to use a case study of the staging of a Spanish-language version of Bonnie and Clyde the Musical to illustrate the importance of the translator’s job as a dramaturg. By analysing a collection of scenes and songs from the eponymous musical (Bonnie and Clyde the Musical), along with a theoretical and dramatic review placed in a historical context, a contextual basis will be provided enabling readers to grasp the universality of the musical theatre genre. The author, through their own personal experience with musical theatre, can highlight how practice-based theories will help formulate more effective theories of how musicals can be translated. To assist this case study, the author has coined a halfway domestication approach, that will be used within the methodology. It will use translation as a tool to blur the lines between translator, dramaturg and actor and describe the balance between domestication and foreignisation when approaching the target texts. The study will illustrate that, while undertaking this role, the translator prioritises both the audience and the actor. To summarise, this dissertation will use personal experience alongside a theoretical and translatorial framework to contribute towards the research gap in the ‘translator as a practitioner’ argument. It will illustrate how translating for musical theatre, specifically for singability is paramount in this genre.